Pengaruh Citra Destinasi & Persepsi Risiko terhadap Minat Kunjung Ulang: Peran Kepuasan Wisatawan pada Pendaki Gunung Prau Via Patak Banteng - Amalia Romadhani; Rahayu, Tri Septin Muji; Anggara, Ali Akbar; Miftahuddin, Muchammad Agung; Innayah, Maulida Nurul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how destination image and perceived risk influence hikers’ revisit intention, with tourist satisfaction as a mediating variable, in the context of Mount Prau hiking route via Patak Banteng. Using a quantitative approach, data were collected online through a Google Form questionnaire distributed to respondents who had hiked the route at least twice, ensuring adequate experience for evaluation. The analysis employed PLS-SEM to assess measurement validity and to test direct and indirect relationships among constructs. The findings indicate that destination image significantly strengthens tourist satisfaction and directly increases revisit intention. Tourist satisfaction also plays a crucial role in shaping revisit intention and mediates the effect of destination image on revisit intention, indicating that revisit intention is largely driven by how hikers evaluate their actual experience after visiting. Conversely, perceived risk does not significantly affect satisfaction or revisit intention, and satisfaction does not mediate the risk–revisit relationship. Practically, strengthening emotional-visual impressions, improving facilities, managing crowding, and reinforcing safety management are strategic priorities to enhance satisfaction and sustain revisit intention for nature-based adventure destinations.